Annular pancreas: the failure of side-to-side gastrojejunostomy anastomosis and the success of repair with Roux-en-Y gastrojejunostomy (Medical Journal of Indonesia, 2015)
Annular pancreas is a rare congenital anomaly characterized by a partial or complete encirclement of ectopic pancreas tissue around the duodenum. We report a case of annular pancreas in a 15 day-old infant admitted to the hospital with complaints of profuse and recurrent vomiting and loss of body weight. Non-contrast abdominal X-ray showed a dilated stomach with bubbles formation around the upper abdomen. An obstruction was noted and open laparotomy was performed. Upon laparotomy, pancreatic ring encircled the proximal duodenum causing an obstruction. Side-to-side gastrojejunostomy was performed and passage through the bypass was satisfactory. Four days after the operation, vomiting and bulging abdomen ensued. Contrast abdominal X-ray demonstrated filling defects at the level of obstruction and the anastomosis made. Anastomotic stricture was suspected and thus was corrected using Roux-en-Ygastrojejunostomy procedure. Postoperative course in this patient was satisfactory and patient was discharged after 24 days of hospitalization.